2019
DOI: 10.1016/j.quascirev.2018.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Middle–Late Pleistocene landscape evolution of the Dover Strait inferred from buried and submerged erosional landforms

Abstract: Prominent landforms, either buried or preserved at the seafloor, provide important constraints on the processes that led to the opening and present-day configuration of the Dover Strait. Here, we extend previous investigations on two distinct landform features, the Fosse Dangeard and Lobourg Channel, to better understand the poly-phase history of their formation and inferences for the opening and Pleistocene evolution of the Dover Strait.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Although slip rates of active faults are very low (on the order of 0.1 mm/yr, see above) some active fault systems are known to be able to host rare but significant earthquakes such as the Rhine Graben Faults (both borders and internal basin faults), some western Alps faults (Higher Durance, Belledone), Frontal external Alps or Pyrenees faults (North Pyrenean zone, MDF and western Provence E-trending thrusts). In old Paleozoic rocks, some major crustal faults (long and rooted) are also prone to rarely produce significant earthquakes such as the frontal zone of Hercynian orogeny [North Artois-shear zone: Jomard et al, 2017, García-Moreno et al, 2019 probably associated with the M w ∼ 6, earthquake of 1580, or the Sillon Houiller Fault zone in western Massif Central (several hundred km long, see location on Figure 2), or the South Armorican shear zone in Brittany, where no paleoseismic evidence has been found although some Quaternary deformations have been mentioned [Baize et al, 2002, Kaub, 2019, and one of the strongest historical earthquake reported in metropolitan France (1799 Bouin earthquake, M w ∼ 6, see location on Figure 2).…”
Section: Potential For Surface Faulting Associated With Significant Earthquakes In Metropolitan Francementioning
confidence: 99%
“…Although slip rates of active faults are very low (on the order of 0.1 mm/yr, see above) some active fault systems are known to be able to host rare but significant earthquakes such as the Rhine Graben Faults (both borders and internal basin faults), some western Alps faults (Higher Durance, Belledone), Frontal external Alps or Pyrenees faults (North Pyrenean zone, MDF and western Provence E-trending thrusts). In old Paleozoic rocks, some major crustal faults (long and rooted) are also prone to rarely produce significant earthquakes such as the frontal zone of Hercynian orogeny [North Artois-shear zone: Jomard et al, 2017, García-Moreno et al, 2019 probably associated with the M w ∼ 6, earthquake of 1580, or the Sillon Houiller Fault zone in western Massif Central (several hundred km long, see location on Figure 2), or the South Armorican shear zone in Brittany, where no paleoseismic evidence has been found although some Quaternary deformations have been mentioned [Baize et al, 2002, Kaub, 2019, and one of the strongest historical earthquake reported in metropolitan France (1799 Bouin earthquake, M w ∼ 6, see location on Figure 2).…”
Section: Potential For Surface Faulting Associated With Significant Earthquakes In Metropolitan Francementioning
confidence: 99%
“…Therefore, the shallow-most near-shore parts of presently submerged continental shelves extend over a considerable area globally and represent an important and often poorly studied geological environment. Due to the steadily increasing interest of the geological and archaeological research communities in shallow, presently submerged, and often buried landscapes [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], accurate depth conversion is crucial for future geological studies and paleoenvironmental reconstructions in such settings. We investigate an example of a transgressed and submerged alluvial plain in the Bay of Koper (Gulf of Trieste, northern Adriatic Sea; Figure 1) to provide sound velocity values for thin (up to 20 m thick) Quaternary sediments deposited in terrestrial-marine sedimentary environments located in shallow near-shore environments a few tens of meters deep.…”
Section: Introductionmentioning
confidence: 99%